Comparing domain interactions within antibody Fabs with kappa and lambda light chains. Issue 7 (2nd October 2016) - Toughiri, Raheleh; Wu, Xiufeng; Ruiz, Diana; Huang, Flora; Crissman, John W.; Dickey, Mark; Froning, Karen; Conner, Elaine M.; Cujec, Thomas P.; Demarest, Stephen J.
ABSTRACT: IgG antibodies are multi-domain proteins with complex inter-domain interactions. Human IgG heavy chains (HCs) associate with light chains (LCs) of the κ or λ isotype to form mature antibodies capable of binding antigen. The HC/LC interaction involves 4 domains: VH and CH1 from the HC and VL and CL from the LC. Human Fabs with κ LCs have been well characterized for their unfolding behaviors and demonstrate a significant level of cooperativity and stabilization when all 4 domains are intact. Very little is known regarding the thermodynamic properties of human Fabs with λ LCs. Here, we dissect the domain contributions to Fab stability for both κ and λ LC-containing Fabs. We find the cooperativity of unfolding between the constant domains, CH1/Cλ, and variable domains, VH/Vλ, within λ LC-containing Fabs is significantly weaker than that of κ LC-containing Fabs. The data suggests there may not be an evolutionary necessity for strong variable/constant domain cooperativity within λ LC-containing Fabs. After investigating the biophysical properties of Fabs with mismatched variable and constant domain subunits (e.g., VH/Vκ paired with CH1/Cλ or T cell receptor Cα/Cβ), the major role of the constant domains for both κ- and λ-containing Fabs may be to reduce the hydrophobic exposure at the VH/VL interface. Even though Fabs with these non-native pairings were thermodynamically less stable, they secreted well from mammalian cells as well behaved monodisperse proteins, which was in contrast to what was observed with the VH/Vκ and VH/Vλ scFvs that secreted as a mixture of monomer and aggregates.